A UAV Coverage Path Planning Method Based on a Diameter–Height Model for Mountainous Terrain - Nan Zhang; Linkai Yue; Qiang Zhang; Chaojun Gao; Bingbing Zhang; Yonghuan Wang (Applied Sciences)
Most unmanned aerial vehicles (UAVs) nowadays engage in coverage missions using coverage paths with simple patterns that are limited in two-dimensional space, ignoring the elevation features of mountainous terrain intentionally, resulting in losing details and increasing the coverage path density and the UAV energy consumption. To address these problems, a coverage path planning method based on the DH (Diameter–Height) model for mountainous terrain is proposed. Firstly, a DH model is proposed for simplifying the 3D map construction of mountainous terrain. Secondly, in virtue of the DH model, the 3D map is partitioned into sub-regions. The equal-interval spiral ascent path and parallel circular coverage path are generated for covering the mountainous terrain with conformal coverage effects. A coverage path connection method with trajectory minimization and obstacle avoidance is proposed in the final path connection stage. The simulation experiments have demonstrated the feasibility and effectiveness of the proposed method and verified that the generated coverage path has the advantages of conformal coverage effects, trajectory minimization, and obstacle avoidance. The comparative experiment has also demonstrated the advantages of the proposed method in terms of UAV energy savings.